TINGKAT PEMAHAMAN DAN KENDALA PENUMPANG MENGGUNAKAN MESIN SELF CHECK-IN DI BANDARA ADI SOEMARMO - Enjelika Enjelika (ADISAM PUBLISHER, 2024)
The advancement of information and communication technology, especially self check-in machines, has significantly improved efficiency and service quality at airports, including Adi Soemarmo International Airport in Surakarta. While these innovations are intended to reduce long queues at check-in counters, many passengers still face difficulties in using the machines. This study aims to evaluate both the utilization and challenges of the self check- in service to enhance its effectiveness and passenger comfort, contributing to the development of more modern airport services. Using a quantitative approach, the research assesses passenger understanding of self check-in machines at the airport. Data was collected from 100 respondents through purposive sampling and analyzed using descriptive percentage methods. Validity and reliability tests ensured the accuracy and consistency of the questionnaires. Conducted from August to September 2023, the study found that passenger understanding of the self check-in service was generally knowledgeable, with an average score of 56.88%, indicating a good grasp of the machines' basic features. However, challenges such as technical issues, lack of usage instructions, and limited staff assistance persist. Improving these supporting facilities is essential for enhancing the passenger experience with self check-in services